Study of comparison of maternal and fetal outcome of elective repeat caesarean versus vaginal birth in women after one prior lower segment caesarean section - ., Latika; Kaur, Gurcharan; Hooda, Reetu; Singh, Sukhbir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean section is almost one of the oldest operation in surgery with its origin lost in antiquity and ancient mythology. A heightened awareness must occur regarding the decision to perform the first caesarean section. Therefore, a study was planned to compare maternal and perinatal outcome between VBAC and repeat elective LSCS in prior one LSCS patients and their complications. Methods: The study was undertaken in the department of Obstetrics and Gynecology at Kasturba hospital, Delhi. Total of one hundred (100) cases of previous one LSCS who were eligible for vaginal delivery were recruited and randomized in two groups (VBAC and repeat elective LSCS). Each group was having fifty (50) patients and prospective study was performed. Results: It was observed that majority of the patients in group I (56%) and group II (40%) were in the age group of 20 to 24 years. Majority of the participants in both the groups were Muslims and majority of them were illiterate. Most of them were in the 39 to 40 weeks of gestation at the time of admission in the hospital. It was found that maximum number of neonates in Group I (80%) & Group II (76%) weighed between 2501-3000 grams. No maternal or perinatal death observed. Conclusions: Vaginal Birth After Caesarean section (VBAC) has always remained a domain of controversies and dilemma in obstetrics. However with improved maternity care, close fetal monitoring and institutional delivery for a previous one caesarean section, VBAC is considered safer than repeat elective caesarean section in a carefully selected patient.